EFEK KOMPOSISI MEDIA HIDROGANIK MENGGUNAKAN BIOCHAR DAN DOSIS VERMIKOMPOS PADAT DAN CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN ANDEWI (Lactuca Sativa L) - baltar ardyah pramesti; Nurhidayati Nurhidayati; Novi Arfarita (AGRONISMA, 2020)
This study aims to determine the interaction effect between the various composition of the growing medium and the dose of vermicompost on the growth and yield of lettuce (Lactuca sativa L). hydroganiclyThis research used factorial randomized block design with two factors. The first factor is the composition of the growingÂ  media (M) which consisted of two levels, namely: M1: Cocopeat (55%), Biochar (15%), and Sand (30%), M2: Cocopeat (55%), Biochar (30%), and Sand (15%). The second factor is the vermicompost dose (V) which consisted of five levels, namely: V0: Without Vermicompost (using inorganic fertilizer AB mix), V1: 50 gram /pot, V2: 100 gram /pot, V3: 150 gram /pot, V4: 200 grams /pot, V5: 250 grams /pot. The observed variables included plant height, number of leaves, leaf area and plant yield variables. The results showed that the composition of the growing media gave different growth and yield of lettuce, where the composition of the growig media composition of M2 (growing media, cocopeat 55%, biochar 30% and sand 15%) using inorganic fertilizer gave the highest plant height but was not significantly different with vermicompost treatment. Interaction of the composition of the growing Â medium and vermicompost dose did not have a significant effect on the leaf area of the andewi plant. The highest total fresh weight of plant biomass was found in the treatment of M2 (growing media composition of cocopeat 55%, Biochar 30%, sand 15%) with inorganic nutrients by 57.55 grams/plant, but not significantly different from some treatments (composition of growing media cocopeat 55%, Biochar 15%, sand 30% with vermicompost dose 200-250 g / pot. Cocopeat growing media 55%, 30% biochar and 15% sand at a dose of 250 g / pot tend to provide fresh weight results of the highest economic value but not significantly different from the dose of 100-200 g / pot.